Reporting guidelines used varying methodology to develop recommendations - Schlussel, MM; Sharp, MK; de Beyer, JA; Kirtley, S; Logullo, P; Dhiman, P; MacCarthy, A; Koroleva, A; Speich, B; Bullock, GS; Moher, D; Collins, GS (Elsevier, 2023)
Background and Objectives We investigated the developing methods of reporting guidelines in the EQUATOR (Enhancing the QUAlity and Transparency Of health Research) Network's database.